Tinjauan Kemampuan Teknik Dasar Sepak Takraw di Balai Baru Klub - Prananda, Rafix (Jurnal Gladiator, 2026)
This research was motivated by the lack of attention of trainers in teaching the basic techniques of sepak takraw. There are still players who are not able to carry out the basic techniques of sepak takraw due to their weak physical abilities, not being able to perform basic sepak takraw techniques correctly, the lack of basic teaching technique training programs provided. and not being able to use the basic technique of playing head-on when playing sepak takraw. This research uses a type of research approach, namely descriptive research. The population of this study was all the sepak takraw players at the new balai club, with a research sample of 15 people. The data collection technique used was testing and documentation, then the data was processed using a difference test (t-test) using the help of SPSS 20.0 for Windows. Based on data analysis on the level of basic soccer technical skills, the mean value (average) = 28.53 and standard deviation = 3.961. The basic technical ability level of turtle football obtained a mean (average) value = 24.06 and standard deviation = 1.980. The basic technical ability level for thigh kicks obtained a mean (average) value = 31.13 and standard deviation = 3.602. The basic technical ability level for playing heading obtained a mean (average) value = 23.13 and standard deviation = 2.065. It can be concluded that the review of the basic sepak takraw technical abilities of the new ball club's sepak takraw players has improved compared to before.